2011
DOI: 10.1007/s12275-011-0519-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antibiotic resistance determinants in oral biofilms

Abstract: Oral biofilms contain numerous antibiotic resistance determinants that can be transferred within or outside of the oral cavity. The aim of this study was to evaluate the prevalence and the relative level of antibiotic resistance determinants from oral biofilms. Oral biofilm samples that were collected from healthy subjects and periodontitis patients were subjected to qualitative and quantitative analyses for selected antibiotic resistance determinants using PCR. The prevalence of tet(Q), tet(M), cfxA, and bla … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 38 publications
4
24
0
Order By: Relevance
“…Knapp et al (2010) showed that resistance to beta-lactamases, tetracyclines, and erythromycins in soil collected over a period of 70~years, significantly increased. A similar approach was applied to study the prevalence of resistance genes in oral biofilms (Kim et al, 2011) and very recently to study fluoroquinolone resistance in fecal samples of Vietnamese children (Vien le et al, 2012). The main drawback to using targeted PCR-based metagenomics is that the results are skewed towards known resistance genes and mechanisms.…”
Section: Metagenomics To Characterize the Amr Reservoirmentioning
confidence: 99%
“…Knapp et al (2010) showed that resistance to beta-lactamases, tetracyclines, and erythromycins in soil collected over a period of 70~years, significantly increased. A similar approach was applied to study the prevalence of resistance genes in oral biofilms (Kim et al, 2011) and very recently to study fluoroquinolone resistance in fecal samples of Vietnamese children (Vien le et al, 2012). The main drawback to using targeted PCR-based metagenomics is that the results are skewed towards known resistance genes and mechanisms.…”
Section: Metagenomics To Characterize the Amr Reservoirmentioning
confidence: 99%
“…In one study, 509 different bacteria were detected in periodontal samples, but only 29 of these were found among the 560 intestinal- or fecal bacteria isolated, illustrating this point (29). Furthermore, to our knowledge only narrow spectrum beta-lactamases, AmpC beta-lactamases or unspecified TEM-genes have been detected in plaque of patients with periodontitis or in plaque samples from the normal population (20, 3032). The R. aquatilis with the ESBL gene bla RAHN-1/2 identified in the present material is thus, to our knowledge, a novelty.…”
Section: Discussionmentioning
confidence: 88%
“…Antibiotic therapy to treat gram-negative bacteria promotes growth of multiresistant bacteria in ulcers. Dental biofilms may serve as a reservoir of bacteria and antimicrobial resistance determinants [3]. Antibiotic-resistant bacteria, such as those that produce β-lactamase, are more prominent in periodontitis [4].…”
Section: Descriptionmentioning
confidence: 99%